(untitled) (Research, Society and Development, 2021)
Objective: To describe the epidemiological profile of patients with Gestational Trophoblastic Disease (DTG) in Sergipe. Methods: This is an observational, descriptive, collaborative study, carried out with female patients diagnosed with GDD through the application of a questionnaire. 86 women with GDD treated at the referral center in Sergipe, at the University Hospital of the Federal University of Sergipe (HU-UFS), were evaluated. Results: After analyzing the 86 questionnaires included, it was observed that most of the studied patients are women aged 35 years or over (57.1%), brown skin was the most prevalent (77.8%) and in great Catholic (52.7%). As for the level of education up to high school, it was the most common (37.2%), more than half of whom had already had a previous pregnancy (60.5%). Most of them have a partnership (92.5%) monthly family income of up to 1 minimum wage (73.6%) and residents of the interior of the state of Sergipe (70.0%). Conclusion: The profile drawn was women aged 35 years or older, mixed race, Catholic, with schooling up to complete high school, with a previous pregnancy history, with a present partnership, with monthly income up to 1 minimum wage and who come from interior of Sergipe to receive treatment at the State Reference Center for DTG.